Roll‐to‐Roll Dry Transfer of Large‐Scale Graphene. Issue 3 (17th November 2021) - Hong, Nan; Kireev, Dmitry; Zhao, Qishen; Chen, Dongmei; Akinwande, Deji; Li, Wei
Abstract: A major challenge for graphene applications is the lack of mass production technology for large‐scale and high‐quality graphene growth and transfer. Here, a roll‐to‐roll (R2R) dry transfer process for large‐scale graphene grown by chemical vapor deposition is reported. The process is fast, controllable, and environmentally benign. It avoids chemical contamination and allows the reuse of graphene growth substrates. By controlling tension and speed of the R2R dry transfer process, the electrical sheet resistance is achieved as 9.5 kΩ sq −1, the lowest ever reported among R2R dry transferred graphene samples. The R2R dry transferred samples are used to fabricate graphene‐based field‐effect transistors (GFETs) on polymer. It is demonstrated that these flexible GFETs feature a near‐zero doping level and a gate leakage current one to two orders of magnitude lower than those fabricated using wet‐chemical etched graphene samples. The scalability and uniformity of the R2R dry transferred graphene is further demonstrated by successfully transferring a 3 × 3 in 2 sample and measuring its field‐effect mobility with 36 millimeter‐scaled GFETs evenly spaced on the sample. The field‐effect mobility of the R2R dry transferred graphene is determined to be 205 ± 36 cm 2  V −1 . Abstract : A Roll‐to‐roll process is developed for dry transfer of large‐scale graphene. With peeling speed and tension control, surface resistance of 9.5 kΩ sq −1 is achieved on polyethylene terephthalate/ethylene vinyl acetate, allowing the fabrication of flexible graphene‐based field effect transistors with 100 times lower gate leakage current and near‐zero doping level compared with those fabricated using wet etched graphene samples.